Low-fluence Q-switched Nd: YAG 1064-nm laser and intense pulsed light for the treatment of melasma - V. Vachiramon (2018)
© 2014 European Academy of Dermatology and Venereology. Background Low-fluence Q-switched Nd:YAG 1064 nm laser (LFQS) and intense pulsed light (IPL) have been shown to be effective in the treatment of melasma. LFQS can target deeper pigment, while IPL can target a wide range of cutaneous structures. However, there is limited information on efficacy and side-effects of the combined treatment. Objective To compare the efficacy and safety of combined LFQS and IPL therapy with LFQS monotherapy in the treatment of melasma. Methods Twenty female patients with mixed-type melasma on both cheeks were treated with LFQS on full face for five sessions at 1-week intervals. One side of the face was randomly assigned to receive additional three sessions of IPL treatments at 2-week intervals. Patients were evaluated 12 weeks after the last treatment. Outcome measures include the assessment by colorimeter and calculated as relative lightness index (R∗LI), modified Melasma Area and Severity Index (mMASI), patient satisfaction and adverse effects. Results Eighteen patients completed the study. Both sides of the face showed significant improvement of R∗LI and mMASI. A more rapid improvement of R∗LI and mMASI was observed on combined side. At the end of treatment, 55% improvement and 37% improvement of R∗LI was observed on combined side and monotherapy side respectively. The overall patients' satisfaction was in favour of the combined side. Recurrence occurred on both sides but there was still a significant decrease compared to baseline. No serious side effect was noted. Conclusion The combination of LFQS and IPL results in faster clearance of melasma and is more effective than LFQS alone for melasma treatment. However, recurrence is still inevitable.